2022
DOI: 10.3390/cancers14246122
|View full text |Cite
|
Sign up to set email alerts
|

Landscape of Savolitinib Development for the Treatment of Non-Small Cell Lung Cancer with MET Alteration—A Narrative Review

Abstract: Non-small cell lung cancer (NSCLC) is increasingly being treated with targeted therapies. Savolitinib (Orpathys®) is highly selective mesenchymal epithelial transition (MET)–tyrosine kinase inhibitor (TKI), which is conditionally approved in China for advanced NSCLC with MET exon 14 skipping mutations (METex14). This article summarizes the clinical development of savolitinib, as a monotherapy in NSCLC with METex14 mutation and in combination with epidermal growth factor receptor (EGFR) inhibitor in post EGFR–T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…Savolitinib, a highly selective small-molecule MET-TKI, received conditional approval by the China National Medical Products Administration (NMPA) in 2021 for the clinical treatment of NSCLC with MET exon 14 skipping mutations. [6][7][8] Previous reports have also indicated that savolitinib is effective in NSCLC patients with MET amplification after previous treatment with EGFR-TKIs. 9 However, the efficacy of MET-TKIs, especially savolitinib, is not fully assessed in MET fusion-positive NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Savolitinib, a highly selective small-molecule MET-TKI, received conditional approval by the China National Medical Products Administration (NMPA) in 2021 for the clinical treatment of NSCLC with MET exon 14 skipping mutations. [6][7][8] Previous reports have also indicated that savolitinib is effective in NSCLC patients with MET amplification after previous treatment with EGFR-TKIs. 9 However, the efficacy of MET-TKIs, especially savolitinib, is not fully assessed in MET fusion-positive NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…MET is known as the hepatocyte growth factor receptor and is located at the long arm of chromosome 7( 75 ). MET contributes to nerve and muscle formation and is involved in embryogenesis and wound healing.…”
Section: Gene Mutation and Targeted Therapy In Sub-centimeter Lung Ca...mentioning
confidence: 99%
“…There are a few more type Ib Met TKIs currently under clinical investigation, (savolitinib, APL-101, and SAR125844). Savolitinib (also known as AZD6094 and volitinib) is a highly selective Met TKI that is conditionally approved in China for advanced NSCLC with MET-exon-14-skipping mutations [89]. In a pivotal phase 2 trial (NCT02897479), savolitinib as a monotherapy demonstrated notable clinical responses and a well-tolerated safety profile in Chinese patients with pulmonary sarcomatoid carcinoma (PSC), brain metastasis, and other NSCLC subtypes positive for MET exon 14 mutations [90].…”
Section: Type Ib Met Tkismentioning
confidence: 99%